Little evidence for association of the glaucoma gene MYOC with open-angle glaucoma. Issue 5 (6th May 2010) - Sohn, Seongsoo; Hur, Wonhee; Choi, Young Ran; Chung, Yun Shin; Ki, Chang-Seok; Kee, Changwon
Abstract : Background/aim: To determine if overexpression of the glaucoma gene MYOC is involved in the development of open-angle glaucoma (OAG) and if its promoter variants are associated with glaucoma in the Korean population. Methods: Human trabecular meshwork cells were cultured in the presence of ophthalmic steroids such as fluorometholone, fluorometholone acetate, dexamethasone, prednisolone acetate and rimexolone. The cells were cultured at a hydrostatic pressure of 32 mm Hg above atmospheric pressure and induction of MYOC was evaluated by northern blot analysis. Genomic DNA was extracted from blood samples obtained from 74 normal controls and 168 unrelated Korean patients with OAG, including primary OAG, normal tension glaucoma and steroid-induced glaucoma. A 461 base pair (bp) DNA fragment of the MYOC promoter region was amplified using PCR and its genotype was analysed by directly sequencing the product. Results: The potencies of steroid eye drops in MYOC induction in vitro was the same regardless of their potential for elevating intraocular pressure in vivo. Hydrostatic pressure had no effect on MYOC induction. A dinucleotide repeat polymorphism and three single nucleotide polymorphisms were identified, but no obvious differences in the genotype distribution and allele frequency of the variants between the control group and any type of OAG were observed. Conclusion: Our data suggest that MYOC overexpression is not a cause or an effect of intraocular pressure elevation and that MYOC itself is not associated with OAG.